2008
DOI: 10.1242/dev.009662
|View full text |Cite
|
Sign up to set email alerts
|

Common functions of central and posterior Hox genes for the repression of head in the trunk ofDrosophila

Abstract: Hox genes are localised in complexes, encode conserved homeodomain transcription factors and have mostly been studied for their specialised functions: the formation of distinct structures along the anteroposterior axis. They probably derived via duplication followed by divergence, from a unique gene, suggesting that Hox genes may have retained a common function. The comparison of their homeodomain sequences groups Hox proteins into Anterior, Central and Posterior classes, reflecting their expression patterns i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…Here, we have shown that in Drosophila the expression domain of Optix in eye discs, which runs along the anteriormost medial disc region, maps to the anterior medial dorsal head, where it is required. In addition, OptixNP2631>OptixRNAi adults show defects in the clypeal skeleton (not shown), recapitulating the defects seen in larvae (Coiffier et al, 2008). Therefore, all these results point to six3/Optix as a medial head-patterning gene also during eyeantennal disc development.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Here, we have shown that in Drosophila the expression domain of Optix in eye discs, which runs along the anteriormost medial disc region, maps to the anterior medial dorsal head, where it is required. In addition, OptixNP2631>OptixRNAi adults show defects in the clypeal skeleton (not shown), recapitulating the defects seen in larvae (Coiffier et al, 2008). Therefore, all these results point to six3/Optix as a medial head-patterning gene also during eyeantennal disc development.…”
Section: Discussionsupporting
confidence: 55%
“…segment in Drosophila and the labral and middle head regions in Tribolium. Accordingly, six3/Optix mutant Drosophila larvae show reduced or absent labral-derived head skeletal elements, such as the labral organ and the maxillary segment-derived mouth hooks in Drosophila (Coiffier et al, 2008) and loss of the labrum and anterior vertex bristle in Tribolium (Posnien et al, 2009(Posnien et al, , 2011. Here, we have shown that in Drosophila the expression domain of Optix in eye discs, which runs along the anteriormost medial disc region, maps to the anterior medial dorsal head, where it is required.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…To bypass embryonic lethality and recover bou let mutant larvae, we expressed wild-type HA-Bou in bou let embryos using nulloGAL4, a driver only active at the blastoderm stage (Coiffier et al, 2008). In this way, we obtained bou let mutants now dying at pupariation and presenting discs with reduced size and abnormal shape.…”
Section: Research Articlementioning
confidence: 99%
“…Repression of Distalless (Dll) by abdominal Hox genes (Vachon et al 1992;Gebelein et al 2002), but not more anterior Hox genes, represents a semiparalog-specific target gene (Mann et al 2009). In contrast, the head-specifying gene optix is repressed by most Hox genes, and provides an example of a shared Hox function (Coiffier et al 2008). In principle, because a high degree of specificity is required for only paralog-specific target gene regulation, the types of binding sites used by Hox proteins to regulate these distinct types of target genes may be different (Mann et al 2009).…”
mentioning
confidence: 99%